MutY DNA Glycosylase Protects Cells From Tumor Necrosis Factor Alpha‐Induced Necroptosis. Issue 7 (15th March 2017) - Tran, An Hue Vy; Han, Se Hee; Kim, Joon; Grasso, Francesca; Kim, In San; Han, Ye Sun
ABSTRACT: Numerous studies have implied that mutY DNA glycosylase (MYH) is involved in the repair of post‐replicative mispairs and plays a critical role in the base excision repair pathway. Recent in vitro studies have shown that MYH interacts with tumor necrosis factor receptor type 1‐associated death domain (TRADD), a key effector protein of tumor necrosis factor receptor‐1 (TNFR1) signaling. The association between MYH and TRADD is reversed during tumor necrosis factor alpha (TNF‐α)‐ and camptothecin (CPT)‐induced apoptosis, and enhanced during TNF‐α‐induced survival. After investigating the role of MYH interacts with various proteins following TNF‐α stimulation, here, we focus on MYH and TRADD interaction functions in necroptosis and its effects to related proteins. We report that the level of the MYH and TRADD complex was also reduced during necroptosis induced by TNF‐α and zVAD‐fmk. In particular, we also found that MYH is a biologically important necrosis suppressor. Under combined TNF‐α and zVAD‐fmk treatment, MYH‐deficient cells were induced to enter the necroptosis pathway but primary mouse embryonic fibroblasts (MEFs) were not. Necroptosis in the absence of MYH proceeds via the inactivation of caspase‐8, followed by an increase in the formation of the kinase receptor‐ interacting protein 1 (RIP1)‐RIP3 complex. Our results suggested that MYH, which interacts with TRADD, inhibits TNF‐α necroptotic signaling. Therefore, MYH inactivation is essential for necroptosis via the downregulation of caspase‐8. J. Cell. Biochem. 118: 1827–1838, 2017. © 2017 Wiley Periodicals, Inc. Abstract : MYH, which interacts with TRADD, inhibits TNF‐α necroptotic signaling. MYH inactivation is essential for necroptosis via the downregulation of caspase‐8.